2016
DOI: 10.1159/000443267
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Regular-Dose Imatinib Therapy in Patients with Gastrointestinal Stromal Tumors Undergoing Dialysis

Abstract: The number of cancer patients undergoing dialysis has been increasing, and the number of these patients on chemotherapy is also increasing. Imatinib is an effective and safe therapy for KIT-positive gastrointestinal stromal tumors (GIST), but the efficacy and safety of imatinib in dialysis patients remain unclear. Because clinical trials have not been conducted in this population, more investigations are required. We report on a 75-year-old Japanese man undergoing dialysis who presented with massive tarry stoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…At present, there are few reports about TKI treatment in HD patients. In previous cases, imatinib was given to 7 HD patients (16)(17)(18)(19)(20): in only one case, the plasma concentration of imatinib was measured, and there was no difference between before and after HD (16). Moreover, apparent toxicities of the imatinib for the HD patients have been rarely reported so far (Table 2), which suggests that it is not necessary to modify the dose of imatinib given to CML patients on HD.…”
Section: Discussionmentioning
confidence: 97%
“…At present, there are few reports about TKI treatment in HD patients. In previous cases, imatinib was given to 7 HD patients (16)(17)(18)(19)(20): in only one case, the plasma concentration of imatinib was measured, and there was no difference between before and after HD (16). Moreover, apparent toxicities of the imatinib for the HD patients have been rarely reported so far (Table 2), which suggests that it is not necessary to modify the dose of imatinib given to CML patients on HD.…”
Section: Discussionmentioning
confidence: 97%
“…In another case report, the drug was used as an adjuvant, again without toxicity [ 24 ]. In the last case available, the patient progressed after 4 months but it is unknown if the underlying mutation was sensitive to imatinib [ 25 ]. Among chronic myeloid leukemia patients, in one study a progressive increase of plasma levels of imatinib was reported, causing severe adverse effects requiring dose reduction [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy in dialysis patients is challenging because drug excretion differs from that of non-dialysis patients. Drugs that are excreted by dialysis may show reduced efficacy, while those that are not excreted may cause adverse events [10].…”
Section: Discussionmentioning
confidence: 99%